2010
DOI: 10.1021/ml100143q
|View full text |Cite
|
Sign up to set email alerts
|

A Potent and Selective AMPK Activator That Inhibits de Novo Lipogenesis

Abstract: AMP-activated protein kinase (AMPK) is a heterotrimeric kinase that regulates cellular energy metabolism by affecting energy-consuming pathways such as de novo lipid biosynthesis and glucose production as well as energy-producing pathways such as lipid oxidation and glucose uptake. Accordingly, compounds that activate AMPK represent potential drug candidates for the treatment of hyperlipidemia and type 2 diabetes. Screening of a proprietary library of AMP mimetics identified the phosphonic acid 2 that bears li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 35 publications
1
80
0
Order By: Relevance
“…However, AICAR may be useful in treating humans with acute lymphoblastic leukemia59,60 and cardiac ischemic injury 61,62. Interestingly, another recently described AMPK activator, compound 13, is taken up into the cells and converted to the AMP analog, compound 2, which is a much more potent and specific activator of AMPK when compared to ZMP 63. Compounds of this series are being optimized for oral bioavailability and pharmacokinetics; however, their clinical utility remains to be seen 63…”
Section: Ampk Activatorsmentioning
confidence: 99%
“…However, AICAR may be useful in treating humans with acute lymphoblastic leukemia59,60 and cardiac ischemic injury 61,62. Interestingly, another recently described AMPK activator, compound 13, is taken up into the cells and converted to the AMP analog, compound 2, which is a much more potent and specific activator of AMPK when compared to ZMP 63. Compounds of this series are being optimized for oral bioavailability and pharmacokinetics; however, their clinical utility remains to be seen 63…”
Section: Ampk Activatorsmentioning
confidence: 99%
“…As many pharmacological activators of AMPK, including the biguanides metformin [13] and phenformin [38], the thiazolidinedione peroxisome proliferator-activated receptor (PPAR)γ agonist troglitazone and ciglitazone [122], AICAR [123], the natural products berberine [124], resveratrol [125], and curcumin [126], and the direct activators A-769662 [127] and PT-1 [128] (structures, Fig. 2), have been discussed in details in several recent reviews [10, 129131], we focus here on two of the most recently reported activators, OSU-53 [132] and compound 2 [5-(5-hydroxy-isoxazol-3-yl)-furan-2-phosphnic acid] [133] (structures, Fig. 2).…”
Section: Ampk Modulators As Cancer Therapeutic Agentsmentioning
confidence: 99%
“…One except is A769662, which stimulates b1-containing complexes [29]. Recent research efforts have identified a nucleotide mimetic compound 2 (C2) [30], and its cellpermeable pro-drug C13 [18], as novel and highly potent AMPK activators. C13 is characterized as an a1-selective small molecule activator of AMPK [18].…”
Section: Discussionmentioning
confidence: 99%